Ff-IR Spectroscopic Studies on Lignin from Some Tropical Woods and Rattan - Lau, S; Ibrahim, Ramli (1992)
Klason lignin of four different types of tropical hardwoods and rattan was studied using rT-IR spectroscopy. There were observable differences in the rT-IR spectra of the lignin studied. Lignin from the more durable and more resistant wood were found to contain less guaiacyl groups than that from the softer and less resistant wood. 77re strength and resistance of the wood might be related to its lignin content.